Innovations and the Use of Collimators in the Delivery of Pencil Beam Scanning Proton Therapy - Daniel E. Hyer, PhD; Laura C. Bennett, MS; Theodore J. Geoghegan, MS; Martin Bues, PhD; Blake R. Smith, PhD (International Journal of Particle Therapy, 2021)
Purpose: The development of collimating technologies has become a recent focus in pencil beam scanning (PBS) proton therapy to improve the target conformity and healthy tissue sparing through field-specific or energy-layer–specific collimation. Given the growing popularity of collimators for low-energy treatments, the purpose of this work was to summarize the recent literature that has focused on the efficacy of collimators for PBS and highlight the development of clinical and preclinical collimators. Materials and Methods: The collimators presented in this work were organized into 3 categories: per-field apertures, multileaf collimators (MLCs), and sliding-bar collimators. For each case, the system design and planning methodologies are summarized and intercompared from their existing literature. Energy-specific collimation is still a new paradigm in PBS and the 2 specific collimators tailored toward PBS are presented including the dynamic collimation system (DCS) and the Mevion Adaptive Aperture. Results: Collimation during PBS can improve the target conformity and associated healthy tissue and critical structure avoidance. Between energy-specific collimators and static apertures, static apertures have the poorest dose conformity owing to collimating only the largest projection of a target in the beam’s eye view but still provide an improvement over uncollimated treatments. While an external collimator increases secondary neutron production, the benefit of collimating the primary beam appears to outweigh the risk. The greatest benefit has been observed for low-energy treatment sites. Conclusion: The consensus from current literature supports the use of external collimators in PBS under certain conditions, namely low-energy treatments or where the nominal spot size is large. While many recent studies paint a supportive picture, it is also important to understand the limitations of collimation in PBS that are specific to each collimator type. The emergence and paradigm of energy-specific collimation holds many promises for PBS proton therapy.